Feeling psychologically unsafe at school and university: bullying and youth living with depression in Indonesia - Lafi Munira; Pranee Liamputtong; Pramon Viwattanakulvanid (International Journal of Public Health Science (IJPHS), 2023)
The prevalence of bullying in Indonesia was 41% among students aged fifteen. This study explored the experiences of being bullied at school/university and the psychological trauma of being bullied among youth with mental disorders in Indonesia. The study adopted a qualitative approach by conducting in‐depth one‐on‐one interviews through WhatsApp chat among twenty participants with mental disorders aged 18-25 from five municipalities in Indonesia (Padang, Jakarta, Yogyakarta, Banjarmasin, and Makassar). Data collection process was conducted from January to June 2022. The thematic analysis method was used for data analysis. Findings can be constructed into five themes: i) looking different: physical appearance, ii) sexual bullying, iii) toxic seniority at school/university, iv) unhealthy competition among students at school/university, and v) Being bullied and having mental health problems. Bullying prevention programs at schools and universities in Indonesia are needed to enhance bullying awareness among students and teachers at schools/universities and to achieve safety in schools/universities for students.